Increased Neutrophil Activation and Plasma DNA Levels in Patients with Pre-Eclampsia - Hu, Yae; Li, Hui; Yan, Ruhong; Wang, Can; Wang, Yun; Zhang, Ce; Liu, Meng; Zhou, Tiantian; Zhu, Weipei; Zhang, Hong; Dong, Ningzheng; Wu, Qingyu (Thrombosis and Haemostasis, 2018)
Pre-eclampsia (PE) is a chronic inflammatory disease in pregnancy, which is associated with enhanced blood coagulation and high thrombotic risk. To date, the mechanisms underlying such an association are not fully understood. Previous studies reported high levels of plasma deoxyribonucleic acid (DNA) in PE women, but the cellular source of the circulation DNA remains unknown. In this study, we tested the hypothesis that activated neutrophils undergoing cell death, also called NETosis, may be responsible for the elevated plasma DNA levels in PE women. We analysed plasma samples from non-pregnant, normal pregnant and PE women and found high levels of double-stranded DNA, myeloperoxidase (an abundant neutrophil granular enzyme) and histones (the major nucleosome proteins) in PE-derived samples, indicating increased NETosis in the maternal circulation. The high plasma DNA levels positively correlated with enhanced blood coagulation in PE women. When isolated neutrophils from normal individuals were incubated with PE-derived plasma, an elevated NETosis-stimulating activity was detected. Further experiments showed that endothelial micro-particles, but not soluble proteins, in the plasma were primarily responsible for the NETosis-stimulating activity in PE women. These results indicate that circulating micro-particles from damaged maternal endothelium are a potent stimulator for neutrophil activation and NETosis in PE women. Given the pro-coagulant and pro-thrombotic nature of granular and nuclear contents from neutrophils, enhanced systemic NETosis may represent an important mechanism underlying the hyper-coagulability and increased thrombotic risk in PE.
Keywords: hyper-coagulability; hypertension; micro-particles; NETosis; neutrophils; Pre-eclampsia